Magnetic nanosystem a tool for targeted delivery and diagnostic application: Current challenges and recent advancement - Rarokar, Nilesh; Yadav, Sakshi; Saoji, Suprit; Bramhe, Pratiksha; Agade, Rishabh; Gurav, Shailendra; Khedekar, Pramod; Subramaniyan, Vetriselvan; Wong, Ling Shing; Kumarasamy, Vinoth (International journal of pharmaceutics: X, 2024)
Over the last two decades, researchers have paid more attention to magnetic nanosystems due to their wide application in diverse fields. The metal nanomaterials' antimicrobial and biocidal properties make them an essential nanosystem for biomedical applications. Moreover, the magnetic nanosystems could have also been used for diagnosis and treatment because of their magnetic, optical, and fluorescence properties. Superparamagnetic iron oxide nanoparticles (SPIONs) and quantum dots (QDs) are the most widely used magnetic nanosystems prepared by a simple process. By surface modification, researchers have recently been working on conjugating metals like silica, copper, and gold with magnetic nanosystems. This hybridization of the nanosystems modifies the structural characteristics of the nanomaterials and helps to improve their efficacy for targeted drug and gene delivery. The hybridization of metals with various nanomaterials like micelles, cubosomes, liposomes, and polymeric nanomaterials is gaining more interest due to their nanometer size range and nontoxic, biocompatible nature. Moreover, they have good injectability and higher targeting ability by accumulation at the target site by application of an external magnetic field. The present article discussed the magnetic nanosystem in more detail regarding their structure, properties, interaction with the biological system, and diagnostic applications. [Display omitted] •Magnetic nanoparticles have magnetic properties ranging from 5 to 100 nm.•Magnetic nanosystems (MNs) exhibit promise in diverse biomedical applications.•A summary of MN types, classes, properties, & characterization methods is provided.•Synthesis methods and therapeutic applications of various MNs are also explored.•Magnetic vectorization of cells is a novel approach in the near future.